Co-optation and Counter-narratives: Unpacking the Survival Strategies of Lebanese Political Elites post-October 17 - Makhlouf, Rita Theresia (2025)
This thesis examines how Lebanon’s political elites have employed strategies of co-optation and counter-narratives to survive the wide-scale uprisings in Lebanon on 17 October 2019. It develops a nuanced approach to understand how political elites engage with contention in ways that are not directly repressive but strategically narrated in their discourses. This contributes to further insights in the field of social movements that uncover how power-sharing systems operate in the face of contention. Drawing on a multi-phased analysis conducted between October 2019 and May 2022, the thesis examines the rhetoric and discourse of political elites that aim to delegitimize the uprisings, thereby reducing mass mobilization, increasing sectarian tensions, and reconsolidating power within the system. It shows that the co-optation of Lebanese political elites went beyond the adoption of the protesters' demands to include purposeful irresponsibility, political withdrawal performances, strategic ambiguity in discourse, and the scripting of alternative crises. Simultaneously, it reveals that counter-narratives focused on sectarian populism, securitization arguments, a politicization of the protests, and foreign conspiracy theories, which served to delegitimize the uprisings and shift public discourse. It examines statements from interviews, social media posts, and speeches of Lebanese politicians such as Samir Geagea, Samy Gemayel, Gebran Bassil, Hassan Nasrallah, Saad Hariri, and Walid Jumblatt who represent some of the chief figures of the main sectarian communities in Lebanon. Through an extensive discourse analysis, this thesis demonstrates how these strategies reinforced exclusionary pluralism and elite entrenchment in the system. This thesis assesses the results of the May 2022 parliamentary elections to gauge the success of Lebanese political elites’ strategies of co-optation and counter-narratives. Ultimately, this thesis contributes to an understanding of the political forces that shape contention in Lebanon’s consociational model, thereby shedding light on the entrenched structures that protesters attempt to change.